IMPLEMENTASI SENSOR SUHU DAN ASAP UNTUK DETEKSI DINI KEBAKARAN DI SOLAR CHARGING STATION EV: IMPLEMENTASI SENSOR SUHU DAN ASAP UNTUK DETEKSI DINI KEBAKARAN DI SOLAR CHARGING STATION EV - Sanjaya, Diki Arta; Dewantara, Belly Yan; Winarno, Istiyo (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2024)
Fires at solar-powered electric vehicle charging stations have the potential to cause significant losses, both in terms of material and human casualties. This research aims to design and implement an early fire detection system based on a DS18B20 temperature sensor and an MQ-2 smoke sensor integrated with an Arduino Uno. Temperature and smoke concentration data are monitored in real time, and if values above a threshold are detected, the system issues an alert via a buzzer and visual indicator. Test results indicate that the combination of the two sensors provides better detection accuracy than using a single sensor. This system can be implemented to improve safety at solar-powered electric vehicle charging facilities.